Pengembangan LKS Matematika Berbasis RME Dengan Konteks Budaya Sunda Untuk Meningkatkan Literasi Numerasi Siswa SMP - Kosasih, Fajar Hamzah; Imswatama, Aritsya; Lukman, Hamidah Suryani (Program Studi Pendidikan Matematika Universitas Muhammadiyah Sukabumi (UMMI), 2025)
This study aims to develop a Student Worksheet (LKS) based on Realistic Mathematics Education (RME) with a Sundanese cultural context to enhance students' numeracy literacy skills. The research background stems from the low numeracy literacy of students, attributed to conventional mathematics teaching methods that have not optimally developed these competencies. The research method employs Research and Development (R&D) using the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). Validation results by material experts indicate that the LKS is highly feasible, with an average score of 90.53%, while validation by teaching material experts yields an average score of 95.42% (also categorized as highly valid). The practicality of the LKS was assessed based on teacher evaluations, scoring an average of 93.33%, and student questionnaire responses, with an average score of 82.78%. Effectiveness tests conducted at SMPN 3 Sukabumi City demonstrated a significant improvement in students' numeracy literacy, marked by an average n-gain score of 60%. Based on these findings, it is concluded that the RME-based LKS with a Sundanese cultural context is feasible and effective as a learning support tool to enhance students' numeracy literacy